Brachytherapy for conservative treatment of invasive penile carcinoma in older patients: Single institution experience. Issue 3 (May 2018) - Escande, Alexandre; Maroun, Pierre; Dumas, Isabelle; Schernberg, Antoine; Bossi, Alberto; De Crevoisier, Renaud; Deutsch, Eric; Haie-Meder, Christine; Chargari, Cyrus
Abstract: Background: No study has examined the possibility to perform an organ sparing strategy in older patients with penile carcinoma, and amputation is frequently proposed. We report our experience of interstitial brachytherapy for the conservative treatment of penile carcinoma confined to the glans in patients aged of 70 years and more. Methods: A total of 55 patients candidates to conservative brachytherapy were identified. Median age was 73.8 years (range: 70–95 years). Patients underwent a circumcision then 3–4 weeks later, an interstitial brachytherapy was delivered, median dose of 65 Gy (range 55–74 Gy). Salvage surgery was discussed in patients with histological confirmation of residual/relapsed tumor. Results: With median follow-up of 9.0 years, eight patients (14.5%) experienced a relapse, including five patients with local relapse. Three patients with local relapse only underwent salvage penile surgery, including two partial glansectomies and one total penectomy, and were in second complete remission at last follow-up. Among 55 patients analyzed for late side effects, seven patients (13.0%) presented pain or ulceration, 12 (22.2%) experienced urethral or meatal stenosis requiring at least one dilatation, two patients (3.7%) experienced both ulcerations and urethral complication. Three patients (5.5%) needed partial glansectomy for focal necrosis. At five years, estimated overall survival rate was 74.5% (95%CI: 62.0–87.0%) and local relapse free rate was 91.0% (95%CI: 82.6–99.4%). Conclusion: Brachytherapy is feasible in selected older patients with penile carcinoma, with efficacy and toxicity rates comparable to that of other series in younger patients.